Effects of pounding on adjacent buildings of varying heights during earthquake in Pakistan. Issue 1 (31st December 2016) - Noman, Muhammad; Alam, Bashir; fahad, Muhammad; Shahzada, Khan; Kamal, Muhammad
Abstract: Pounding occurs when the adjacent buildings start vibration out of phase during the seismic activity which causes collision amongst the adjacent buildings. There are many mitigation techniques to avoid or minimize the effects of pounding including the provision of minimum separation gap between the adjacent buildings. Although all codes have provided the minimum separation gap requirements for the buildings, still a lot of study is required on this topic. This research aims at finding the minimum gap requirement for midrise buildings in Pakistan. Adjacent Buildings with different geometry and height are modelled in Sap2000 software with varying gap elements. Pushover and In-elastic time history analysis of these buildings are carried out using ground motion of Kashmir earthquake. Buildings are assumed to be resting on stiff soil. Material and sectional properties are also remained same for all cases. In order to reduce the pounding effects of two buildings, they were attached with each other and top displacements of buildings were compared with separate buildings with inadequate gap. Column shear, maximum peak displacements and square root of sum of squares of maximum peak displacements were studied and the results were plotted graphically. It was found out that pounding can occur up to separation gap of six inch. Maximum pounding occurs at the top floor level of smaller building. The requirement for minimum gap in UBC 97 is found out to be conservative.